Mutational and gross deletion study of the MEN1 gene and correlation with clinical features in Spanish patients - Cebrián, Arancha; Ruiz-Llorente, S.; Cascón, A.; Pollán, M.; Díez, J.J.; Picó, A.; Tellería, D.; Benítez, Javier; Robledo, M. (BMJ, 2003)
Multiple endocrine neoplasia type 1 (MEN1, OMIM 131100) is an autosomal dominant disorder character ised by the combination of endocrine tumours, such as parathyroid tumours, enteropancreatic tumours, anterior pituitary tumours, adrenal gland, and neuroendocrine carci noid tumours, as well as non-endocrine expression, such as lipoma, facial angiofibroma, collagenoma, and ependymoma.1 2 Primary hyperparathyroidism (HPT) is the first manifestation of MEN1 in approximately 90% of patients, although this percentage differed between studies.3 4 Gastri noma is the most frequent enteropancreatic tumour, account ing for approximately 40% of enteropancreatic tumours.2 It has thus been suggested that MEN1 syndrome should be excluded in patients with gastrinoma.5 Prolactinomas account for 20% of MEN1 related pituitary lesions,1 2 while other reported pituitary tumours are relatively uncommon manifes tations of MEN1.1 2 The MEN1 gene is located on chromosome 11q136 7 and was positionally cloned in 1997.8 9 It contains 10 exons and encodes menin, a 610 amino acid protein. Menin is known to be a nuclear protein10 that represses JunD activated transcription11 and interacts with other proteins, such as Smad3,12 nm23,13 and NF-¿B,14 all of which are involved in the regulation of cell proliferation and development. Inactivating germline mutations found in MEN1 families/ patients indicates that the MEN1 gene is a tumour suppressor gene.8 9 More than 200 germline and somatic mutations have been identified to date but no hot spots or genotype phenotype correlations have been observed. Consequently, carriers in a family with MEN1 should be checked periodically for typical and less frequent expressions of the MEN1 syndrome. Taking into account both the absence of hot spots for mutations in the MEN1 gene and the lack of genotype phenotype correlations, it is necessary to establish clinical cri teria in order to increase the detection rate of MEN1 germline mutations. It would therefore be more cost effective to perform MEN1 gene mutation analysis of selected patients, rather than of all patients with apparently MEN1 related tumours. This procedure would also avoid unnecessary anxiety for mutation negative patients.15 In this study, 28 MEN1 patients with a family history and 27 MEN1 suspected patients were screened for MEN1 gene germline mutations such as missense, nonsense, or small deletions or insertions, as well as for gross gene deletions. Subsequently, we measured the association between the pres ence and absence of germline mutation and the age of diagnosis and clinical characteristics.